An Empirical Investigation to analyse the Factors influencing the Consumer Perception regarding Life Insurance policies using Path Analysis - Guru Prahaladhan; D. Umamaheswari (International Journal of Supply Chain Management, 2018)
The insurance companies in the country play a significant facet in enhancing the welfare of the individuals which protects the welfare and life of millions of individuals. The life insurance industry is growing at greater speed after the increase in the FDI limit sanctioned by the government. This research intends to understand the factors influencing the consumer perception regarding Life Insurance Policies.The researcher used convenience sampling method in collating the data from the respondents and the researcher used various statistical tools to analyse the data collated. It is concluded that company perception and client-company relationship are considered as the prime factors in influencing the consumer perception towards life insurance policies. Keywords: Consumer perception, company reputation, Path model